Boko Haram Insurgency in Northern States and Challenges of National Security for Sustainable Development in Nigeria - Nwankwo, Samuel C.; Odunuga, Joseph Oluwafemi (NIU Journal of Humanities; Vol 9 No 4 (2024): NIU Journal of Humanities, Vol. 9 No. 4, December 2024, 2024)
Terrorism and insecurity have remained issues of serious concern in Nigeria, several lives and properties have suffered wanton destruction and despicable hardship on the entire citizenry, as being perpetrated by a terrorist group Boko Haram, which has recently attracted the global and international attention. Consequently, Boko haram insurgency has made a considerable percentage of Nigerians to be sent to their early graves and national security has virtually become a mirage, and thereby impedes sustainable development in Nigeria despite all security measures being put in place by those in authority. Boko Haram dreaded group has been ravaging Northern Nigeria for years now. The group keep on changing their strategies of operations and targets starting from Maiduguri, Yobe, Bauchi, Abuja, Suleja, and other parts of the North. The paper adopted historical and descriptive research approaches to discuss the issues raised and put them in appropriate perspectives.  Therefore, the study was anchored on Cohen and Felson’s Routine Activity theory to undertake an exploration of historical background of Boko Haram, conceptualizing of sustainable development, national development, and impacts of Boko haram sects’ unscrupulous activities on sustainable development in Nigeria.  The work recommended the engagement of dialogue, amnesty, improvement of the wellbeing of the people and total overhauling of the security architecture as possible remedies in promoting sustainable development and security in the Northern states in particular and Nigeria at large. Keywords:   Boko Haram, Northern States, Challenges, National Security, Sustainable Development, Nigeria.